"Ritratto di città": Hearing, Listening, Imagining - Scalfaro, Anna (Musica Docta, 2013)
This article proposes an educational path based on Ritratto di città, a radio composition (1955) by Luciano Berio, Bruno Maderna and Roberto Leydi. Relying on activities that focus on the analysis of both the general structure and specific parts of the composition, the didactic path aims at conveying to students the high image-evoking power of sound, in this case, how music can enhance a ‘visual translation’ of the places described by the narrators in the radio work. The didactic path also provides food for thought about the way in which the emergence of sound reproduction equipment has boosted research and experimentation in the field of musical composition.